THREATS OF DECARBONIZATION PRESSURE OF ESG-COMPETITIVENESS METALLURGICAL ENTERPRISES OF UKRAINE - TKACHENKO, ALLA; KOLESNIK, ELEONORA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article states that the peculiarities of functioning under the conditions of formation of steel surplus, increase of competitive tension and formation of specific forms of competition are complicated for the enterprises of the metallurgical complex.  Being in a state of uncertainty, turbulence and bifurcation requires Ukrainian metallurgical enterprises to pay more attention to identifying and neutralizing possible threats and risks to their competitiveness. It is substantiated that these issues can be resolved only with a clear understanding of the vulnerability of competitiveness. This term can be seen as the ability of metallurgical enterprises to adapt to the changing space of existing threats. Most methods for assessing the vulnerability of the competitiveness of enterprises are fragmentary. The formation of a clear idea of the vulnerability of ESG-competitiveness of enterprises is possible only if the formation of a portfolio of vulnerabilities. The portfolio is a detailed description of the main threats and risks of ESG-competitiveness of enterprises. The necessity of expanding the established list of threats to metallurgical enterprises by supplementing it with a group of threats of decarburization pressure is proved. According to the results of expert assessment and the scale of intensity assessment of decarbonization pressures (according to E. Harrington's method), the vulnerability of ESG-competitiveness of metallurgical enterprises of Metinvest Group (Ukraine) and Arcelor Mittal Kryvyi Rih (Ukraine) was assessed. The threats of decarbonization pressure have been found to have a more vulnerable effect on ArcelorMittal Kryvyi Rih. These threats are unmanageable. Expanding the list of threats to the vulnerability of ESG-competitiveness of enterprises in the context of transformation to a low-carbon economy will help improve the adaptability of enterprises in a changing environment. It will also help them respond quickly to emerging risks and threats.
Keywords: decarbonization; threats of decarbonization pressure; vulnerability of ESG-competitiveness of enterprises; threat assessment